Letting Nebuchadnezzar Speak: The Purpose of the First-Person Narrative in Daniel 4 - Widder, Wendy L (Old Testament Essays, 2019)
This article proposes that the use of first-person narration in the unusual literary structure of Dan 4 creates the most meaningful message for the diaspora audience of the book because of who Nebuchadnezzar was and when the events were purported to occur. It discusses the larger literary context of the chapter and its narrative structure, analyses the text and identifies important elements highlighted by the use of different narrative voices, and considers how the structure shapes the message of the chapter. Nebuchadnezzar was the king who defeated Israel’s God (Dan 1:1–2) and changed life forever for God’s people, yet at the peak of Nebuchadnezzar’s power, that same God humbled him such that he came to acknowledge the superior sovereignty of Israel’s God. By framing the account of this transformation as a proclamation in Nebuchadnezzar’s own words to the entire world, the author of Daniel vindicates the God of Israel before the whole world and transforms the king who embodied opposition to God into the paradigm of what a gentile king ought to be.